Clinical and genomic characterization of Klebsiella pneumoniae in a district hospital in Chengdu, China - Hu, Yiyi; Lu, Xingyu; Sun, Yuyan; Yu, Maowen; Zhang, Lei; Jiang, Jianping; Li, Juan (Frontiers in Microbiology, 2025)
Klebsiella pneumoniae is a significant human pathogen in both hospital and community settings; however, limited data exist regarding its prevalence in district-level hospitals. This study aimed to characterize the drug resistance mechanisms, molecular epidemiology, and virulence profiles of K. pneumoniae in a district hospital in Chengdu, China. A total of 114 clinical isolates were collected between May 2023 and May 2024. Antimicrobial susceptibility testing using the broth microdilution method revealed resistance rates of 14.0–21.1% to third-generation cephalosporins, and 5.3% to carbapenems. Whole-genome sequencing showed that 18.4% (21/114) of the isolates carried ESBL genes, with blaCTX–M–15 (n = 7) being the most common. Six carbapenem-resistant isolates were identified, of which four produced carbapenemases: three harbored blaNDM–5 and one carried blaKPC–2. MLST analysis identified 67 sequence types, with ST23 (n = 9) being the most prevalent. The 21 ESBL-producing isolates were distributed across 15 sequence types, while the six carbapenem-resistant isolates were assigned to four distinct sequence types. Virulence-associated genes were detected at high frequencies, including ybt (39.5%), clb (12.3%), iuc (50.0%), iro (60.5%), rmpA (59.6%), and rmpA2 (36.8%), and were commonly found in ST23 (n = 9), ST412 (n = 6), ST25 (n = 5), ST268 (n = 5), and ST375 (n = 4). In conclusion, K. pneumoniae isolates from this district hospital showed low resistance rates but a worrying high prevalence of virulence genes. This highlights the urgent need for continuous surveillance and early intervention strategies to prevent the emergence of highly virulent and multidrug-resistant strains in healthcare settings.